Acute Effect of Kinesiology Taping on Postural Stability in Individuals With Unilateral Chronic Ankle Instability - Yin, Lulu; Wang, Lin (Frontiers in Physiology, 2020)
Background: Chronic ankle instability (CAI) which characterized by deficient postural control could be improved through kinesiology taping (KT). However, the effect of KT on postural control in CAI individuals is controversial. Therefore, this study aimed to investigate the acute effect of KT on postural control through computerized dynamic posturography (CDP) and self-perceived sensation in CAI individuals . Methods: Participants with CAI received four different ankle treatments randomly, including KT, athletic taping (AT), sham taping (ST), and no taping (NT). A series of postural stability measurements was performed using CDP subsequently. The measurements included sensory organization test (SOT), unilateral stance (US), limit of stability (LOS), motor control test (MCT), and adaption test (ADT). In addition, self-perceived sensation was measured through visual analogue scaling. Repeated measures analysis of variance was conducted to determine whether the difference among KT, AT, ST, and NT was significant，Bonferroni test was used for post hoc analysis. Results: No significant difference was observed for parameters in SOT, US, and LOS in four different taping treatments. In MCT, the amplitude scaling scores of KT were 35.87% lower than NT significantly (p<0.001, 95% confidence interval [CI]=0.548 to 1.795) in forward-small slip and 21.58% lower than ST significantly (p=0.035, 95% CI=0.089 to 3.683) in backward-large slip. In ADT, sway energy scores were 7.59% greater in ST than in AT significantly (p=0.028, 95% CI=-8.343 to -0.320). For perceived stability, KT was greater significantly than ST (p<0.001, 95% CI=0.552 to 1.899) and NT (p<0.001, 95% CI=0.797 to 2.534), and AT was greater significantly than ST (p=0.001, 95% CI=0.423 to 2.246) and NT (p<0.001, 95% CI=0.696 to 2.852). For perceived comfort, KT was greater significantly than AT (p=0.001, 95% CI=0.666 to 3.196) and NT (p=0.031, 95% CI=0.074 to 2.332), and ST was greater significantly than AT (p=0.007, 95% CI=0.349 to 2.931). Conclusion: KT and AT has limited effect to facilitate postural control for CAI individuals during SOT, US and LOS. However, KT and AT could provide effective support to cope with sudden perturbation in MCT and ADT. Moreover, KT provided excellent perceived stability and comfort, whereas AT provided excellent perceived stability but least comfort.